Filme de amido de mandioca incorporado de nanopartículas de selênio biogênicas (bio-SeNPs) para controlar patógenos de origem alimenta - Nogueira, Matheus Henrique (2024)
Developing packaging or films with antibacterial action has been a promising and ecological alternative, which can reduce the waste of perishable food products and the risk of transmission of pathogenic microorganisms. These films with antibacterial action have active nanocomposites incorporated into natural biopolymers that inhibit the growth of microorganisms. Nanoparticles have been a promising alternative to food preservation. The use of selenium nanoparticles (SeNP) has been a current strategy as an antimicrobial component. This research aims to develop a biodegradable cassava starch film with bio-SeNPs that aims for antimicrobial action against food pathogens. We conducted the test to determine the Minimum Inhibitory Concentration (MIC) of bio-SeNPs in different bacteria with satisfactory results. We selected Listeria monocytogenes due to its impact on public health and the food production chain. As a control, the diffusion test was carried out in solid media with bio-SeNPs with the chosen bacteria, observing the formation of an inhibition halo. The cassava starch film was incorporated with 1% and 2% bio-SeNPs using the casting method. We carried out microbiological death curve tests in liquid culture and deposited the L. monocytogenes bacteria under the film at times 0, 3, 6, and 24 hours. To characterize the film, we used techniques such as Differential Scanning Calorimetry (DSC), Thermogravimetry (TGA), Fourier transform infrared spectroscopy (FTIR), Scanning Electron Microscopy (SEM), energy dispersive X-ray spectroscopy (EDX), Spectroscopy (Uv-Vis), Water Vapor Permeability, Colorimeter, swelling test, transparency, biodegradation, and film's applicability on tomatoes. The microbiological death curve test confirmed the antimicrobial activity of the films incorporated with bio-SeNPs, presenting statistically significant results from T6 compared to the control film (without bio-SeNPs). The characterization analysis results confirmed the presence of bio-SeNPs incorporated into the films. The addition of bio-SeNPs maintained the desirable characteristics of the films, such as thermal stability and heat resistance compared to the control film, in addition to being more effective in protecting packaged foods against humidity from the external environment due to the reduction in the permeability rate to water vapor. Color and transparency tests indicated a slight reddish color without interfering with the visibility of the food. Overall, the results are promising, demonstrating the potential application of films with bio-SeNPs in the food industry.